Effect of preparation methods on morphology of active manganese dioxide and 2,4-dinitrophenol adsorption performance - Hua-jun Chen; Wenjie Tian; Wuxiu Ding (Adsorption Science & Technology)
Herein active manganese dioxide was prepared by different methods using KMnO 4 and MnSO 4 ·H 2 O as inorganic precursors. The impact of preparation methods on morphology and adsorption performance of the synthesized products was investigated. The experimental results show that the reaction temperature and pressure had a great effect on the morphology and adsorption performance of active manganese dioxide. The shape of active manganese dioxide prepared at room temperature and pressure was short rod-like while active manganese dioxide synthesized by hydrothermal method was mesoporous fibers and had better adsorption performance. The adsorption behavior of 2,4-dinitrophenol on mesoporous manganese dioxide was well described by Langmuir and Freundlich isotherm equation ( R 2 >0.99) and pseudo-second-order kinetic equation ( R 2 >0.99), so the adsorption process maybe a chemical and monolayer adsorption. The pH of solution had significant effect on the adsorption performance of 2,4-dinitrophenol on mesoporous manganese dioxide. The adsorption capacity was 2.539 mg/g in the condition of pH = 7.